Liquid-gas boundary catalysis by gold/polystyrene-coated hollow titania and the effective location of active sites in liquid-liquid phase-boundary catalyst - Mohd. Ran, Nur Hidayah (2014)
The research described in this thesis is an attempt to synthesize floating catalyst to be used in phase-boundary catalysis for liquid-gas reaction. It is also an attempt to determine the effective location of catalytic active sites in phase-boundary catalyst for immiscible liquid-liquid reaction. Phase-boundary catalysis (PBC) is a heterogeneous catalytic reaction in which the catalyst particles are located at the interphase of either immiscible liquid-liquid or liquid-gas phases. In this research, gold/polystyrene-coated hollow titania was successfully synthesized. The synthesis steps involved hydrothermal synthesis of carbon sphere from sucrose as the template, coating of the carbon sphere with titania, removal of the carbon sphere to produce hollow titania, followed by coating of polystyrene on the surface of hollow titania and the attachment of gold nanoparticles. The results showed that the size of the carbon spheres increased when the concentration of the sucrose increased. The hollow titania obtained by carbon sphere template was found to have smaller diameter than its template and was in the anatase phase. Polystyrene was coated on hollow titania by in-situ polymerization of styrene with aqueous H2O2, while gold was deposited by sputtering deposition technique on the surface of polystyrene-coated hollow titania. It has been demonstrated that gold/polystyrene-coated hollow titania can float on water due to its low density and it is a potential catalyst for liquid–gas boundary catalysis in the oxidation of benzyl alcohol by using molecular oxygen. In this study, some aspects in the determination of the effective location of active sites of PBC in immiscible liquid-liquid system were also studied using NaY, HZSM-5 and TS-1 zeolites as the catalysts in the oxidation of 1-octene and hydroxylation of cyclohexene using aqueous H2O2. Based on experimental results, it is concluded that the effective location of active sites is located on the external surface of zeolites.